Women Playing the Bandura: Challenging Discourses of Nationhood - Ostashewski, Marcia (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
As Ukraine’s national instrument, the bandura evokes contradictory and conflicting national narratives. In this article, the author provides a brief history of the bandura, including its role in Ukraine’s modem nation-building process, its performance practices and issues relating to gender. She examines contexts within which two main bandura performance styles are practiced, by relating them to specific events at the Bandura Festival 2000. Interviews with bandura player Nadia Tarnawska reveal how the Bandura Festival 2000 functions within and as a part of the continuing construction of the instruments history, and discourses of Ukrainianness. Tarnawska’s experiences constitute a poignant illustration of the nature of these discourses in relation to the Bandura Festival 2000, Ukrainian musical production more generally, and wider issues relating to gender and nationhood. For this reason, the author discusses the place of life stories in the larger context of changing musical practices.